Ultrasound-Assisted Production of Xylo-Oligosaccharides From Alkali-Solubilized Corncob Bran Using Penicillium janthinellum XAF01 Acidic Xylanase - Zhou, Mingchun; Fan, Guangsen; Xia, Hanshuo; Zhang, Xiaohan; Teng, Chao; Li, Xiuting (Frontiers in Bioengineering and Biotechnology, 2021)
A novel treatment involving enzymatic hydrolysis using an acidic xylanase coupled with ultrasound was performed to improve the xylo-oligosaccharides (XOS) yield from corncob bran. The acidic xylanase (XynB) was purified to a most suitable pH, temperature, and operational parameters for ultrasound-assisted hydrolysis were determined. A preliminary mechanistic investigation was performed through circular dichroism (CD) spectroscopy, scanning electron microscope (SEM) and a laser particle size analyzer, and the effects of ultrasound on enzyme (XynB) and substrate (corncob bran) were assessed. The results show that the maximum XOS yield was 20.71% when the reaction pH and temperature were 4.3 and 50℃, the ultrasonic parameters were 50kHz and 0.40W/cm2, which was 2.55 fold higher than that obtained using a non-ultrasound-assisted enzymatic preparation. Mechanism studies indicated that ultrasonic pretreatment could reduce the β-fold content and increase the random coil content. Changes in structure and size of substrate were observed. The specific surface area of the XAC molecules is easy to carry out enzymatic reaction, which is beneficial to the production of XOS.